Pemetaan Lokasi Penyebaran Layanan BPJS Kota Palembang Berbasis Sistem Informasi Geografis - Dinny Komalasari; irwansyah ibrahim; Helda Yudiastuti; Rismanto Rismanto (JURNAL ILMIAH INFORMATIKA, 2026)
Along with the development of information technology and increasing levels of public education, this encourages us to use computers as a means of providing information. The need for information has become a basic need for society. One of these is the need for geographic information. GIS (Geographic Information System) technology is a geography-related technology that has the ability to visualize spatial data and its attributes. As the capital of South Sumatra Province, the city of Palembang is always required to provide information on the location of existing public facilities. One public facility frequently sought by the public is hospitals. The lack of information about the location of these hospitals can cause problems in the community. This obstacle was the author's consideration in developing a Geographic Information System for the Distribution of BPJS Services in Palembang City. The method used in developing this software is the Waterfall method. The stages of the Waterfall method include analysis, design, coding, and testing. This research resulted in a geographic information system for the distribution of BPJS services in Palembang City